Productivity Analysis at a Small and Medium Enterprises (SMEs)Focusing on Work Study, Line Balance and Ergonomics - Adi , Saptari; Isa , Halim; Seri Rahayu , Kamat; Nor Akramin, Mohamad (2008)
World-class manufacturing is the term applied to manufactures who can succeed against world-class competition in a global market. In order to remain the market place, there is no room for complacency for any company. The ability to optimize the resources especially the manning and the machines in the assembly line has always been an important competitive factor. The purpose of this project is to analyze the existing productivity and provide the SME management with a tool to assist the decision making on the capacity and manpower planning while at the same time meets the ergonomics standards to ensure employees health and safety. This paper will discuss on the work study method employed to set the standard time, development of the simulation model and the ergonomics assessment on the indoor air quality, noise level, thermal comfort and illumination condition. From the work study, the operator standard time and utilization was able to be determined. In addition, the simulation model provided the opportunity to balance the production line while the ergonomics assessments enabled the employees to work in a safe and healthy working condition. The result of this project will be advantageous for the company to be cost efficient in meeting the ever increasing customer demand while still achieving high productivity.